2014
DOI: 10.4055/cios.2014.6.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Medial Unicompartmental Knee Arthroplasty

Abstract: BackgroundWe report intra- and postoperative complications of unicompartmental knee arthroplasty (UKA).MethodsThis study was conducted on 246 cases of UKA which were performed for degenerative osteoarthritis confined to the medial compartment, from May 2002 to May 2010, for which follow-up periods longer than one year were available. Complications were divided into intra- and postoperative complications. Pre- and postoperative clinical scores, the range of motion, and radiologic findings were analyzed.ResultsC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…Kim et al 43 analyzed 89 patients with complications of various reasons after UKA showed that two cases caused by unexplained pain. Hun et al 44 followed up 246 patients who received UKA for more than 1 year, and the incidence of postoperative complications was 9.8%, a case was revised to TKA for unexplained pain. Bhattacharya et al 45 explained that the reasons of the unexplained pain after Oxford-UKA may be related with the position of prosthesis or soft tissue stimulation, yet there are still a large number of unexplained causes is difficult to find exact reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 43 analyzed 89 patients with complications of various reasons after UKA showed that two cases caused by unexplained pain. Hun et al 44 followed up 246 patients who received UKA for more than 1 year, and the incidence of postoperative complications was 9.8%, a case was revised to TKA for unexplained pain. Bhattacharya et al 45 explained that the reasons of the unexplained pain after Oxford-UKA may be related with the position of prosthesis or soft tissue stimulation, yet there are still a large number of unexplained causes is difficult to find exact reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Bearing replacement with an upsized bearing is typically performed for simple bearing dislocations with an otherwise intact prosthesis. In cases with component loosening revision with a replacement OUKP or total knee arthroplasty is typically performed [8], [9].…”
Section: Discussionmentioning
confidence: 99%
“…K nee arthroplasty is a surgical procedure undertaken to replace the weight-bearing surfaces of the knee joint to restore capacity and function 1 . It can be performed as a partial, also called unicompartmental arthroplasty (UKA, which replaces only the damaged surfaces retaining any undamaged parts) or a total knee arthroplasty (TKA) 2,3 . TKA involves replacement of all three compartments of the knee, known as the medial compartment (inside aspect of the knee), the lateral compartment (outside of the knee), and the patellofemoral compartment (the joint between the patella and the femur) 4 .…”
Section: Introductionmentioning
confidence: 99%